2009
DOI: 10.1111/j.1747-0285.2009.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic and Antiviral Activity Evaluations of Hydroxamic Derivatives of Some Non‐steroidal Anti‐inflammatory Drugs

Abstract: Non-steroidal anti-inflammatory drugs (NSAID) pharmacophores are interesting in designing potential anticancer drugs. Indeed, numerous experimental, epidemiologic and clinical studies suggest that NSAIDs are promising anticancer drugs. Herein, NSAID hydroxamic acids 3a-i were prepared by a new synthetic procedure and evaluated for their antiviral and cytostatic activity against malignant tumor cell lines and normal human fibroblasts (WI38). Antiviral activity evaluation results indicated that 3f had only a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Both methods gave products in similar yields. CAD-benzotriazolides 2 were prepared following our procedure described previously: benzotriazolides of various carboxylic acids were synthesized and transformed to esters, amides or hydroxamic acids [49,50,51,52]. Benzotriazolides 2 (active amides) and PQ-benzotriazolide 5 (active urea) were prepared from the same starting compound BtcCl ( 1 ) and CAD or PQ, in the presence of triethylamine (TEA).…”
Section: Resultsmentioning
confidence: 99%
“…Both methods gave products in similar yields. CAD-benzotriazolides 2 were prepared following our procedure described previously: benzotriazolides of various carboxylic acids were synthesized and transformed to esters, amides or hydroxamic acids [49,50,51,52]. Benzotriazolides 2 (active amides) and PQ-benzotriazolide 5 (active urea) were prepared from the same starting compound BtcCl ( 1 ) and CAD or PQ, in the presence of triethylamine (TEA).…”
Section: Resultsmentioning
confidence: 99%
“…The WHO has indicated that there is no evidence to confirm an aggravation of COVID-19 infection with the administration of NSAIDs [30,31]. In fact, it has been reported that some NSAIDs could have some type of activity against viruses such as VZV [32], HCMV [32], HSV-1 [33], influenza virus A⁄ H1N1 subtype [34,35], VSV [36,37], EBOLA [38,39], HIV [40], JEV [41], CHIKV [42], SARS-CoV-1 [43], and recently against SARS-CoV-2 [35,44,45]. Additionally, many studies have been carried out that propose various targets for blocking virus recognition, importation and replication processes through the use of reused drugs, immunotherapies, interference strategies and various inhibitory compounds [46].…”
Section: Introductionmentioning
confidence: 99%
“…1) were prepared following a previously published procedure (5,6). All analytical and spectral data were in agreement with the previously published results.…”
Section: Nsaid Hydroxamic Acids Namely N-hydroxy-2-(4-isobutyl-phenymentioning
confidence: 53%